Usefulness of Endoscopic Indices in Determination of Disease Activity in Patients with Crohn’s Disease - Marcin Kucharski; Jacek Karczewski; Dorota Mańkowska-Wierzbicka; Katarzyna Karmelita-Katulska; Elżbieta Kaczmarek; Katarzyna Iwanik; Piotr Rzymski; Marian Grzymisławski; Krzysztof Linke; Agnieszka Dobrowolska (Gastroenterology Research and Practice)
Background. Assessment of endoscopic activity of Crohn’s disease (CD) is of growing importance both in clinical practice and in clinical trials. The study aimed to assess which of the endoscopic indices used for evaluation of mucosal changes correlates with the currently used clinical indices for determination of disease activity and with the results of histopathological examination. Study. A group of 71 patients with CD and 52 individuals without a diagnosis of GI tract disease as a control group were investigated, considering clinical and histological severity of the disease and the severity of inflammatory changes in the bowel. Evaluation was conducted with the use of clinical, endoscopic, and histopathological indices. Endoscopic indices were then correlated with different clinical and histopathological indices with the aim of finding the strongest correlations. Results and Conclusions. Correlation between the clinical disease activity and the severity of endoscopic lesions in CD was shown in this study to be poor. The results also indicate that the optimal endoscopic index used in the diagnostic stage and in the assessment of treatment effects in CD is Simple Endoscopic Score for Crohn’s Disease (SES-CD).